Hydrochemical assessment of borehole water in Effurun, Delta state Niger Delta, Nigeria: implications for public health and safety - Odunayo Tope Ojo; Chiaka Joy Ike; Adegoke Ige Aladeboyeje; Olayiwola Grace Olaseeni; Olumuyiwa Femi Adewumi (Discover Geoscience)
Abstract Borehole water plays a critical role in providing drinking water in Effurun, Delta State, Nigeria. However, concerns about potential contamination from both natural and anthropogenic sources necessitate regular groundwater quality assessments. This study evaluates the hydrochemical properties of borehole water to ensure public health safety and to understand the groundwater's suitability for consumption. The aim of this study is to assess the quality of borehole water in Effurun by analyzing major ions, trace metals, and other hydrochemical parameters, and to compare the findings with WHO and NSDWQ drinking water standards. Ten borehole water samples were collected from various locations across Effurun. Hydrochemical analyses were conducted to measure cations (calcium, magnesium, sodium, potassium), anions (chloride, bicarbonate, sulfate, nitrate), and trace metals (lead, copper, zinc, manganese). Statistical analysis and spatial mapping were employed to evaluate the distribution of ion concentrations and identify areas of concern. Calcium levels in the boreholes ranged from 29.95 mg/L to 64.50 mg/L, while magnesium levels were more consistent, ranging between 9.50 mg/L and 14.20 mg/L. Sodium and potassium showed moderate correlations with calcium. Chloride levels varied widely, indicating potential contamination from seawater intrusion or industrial discharge. Elevated sulfate and nitrate concentrations pointed to agricultural runoff. Trace metals, particularly lead, exceeded safety limits, with lead concentrations ranging from 0.092 mg/L to 0.127 mg/L, posing significant health risks. Spatial analysis revealed varying ion concentrations across Effurun, with higher calcium and magnesium levels near water bodies, suggesting local geology's influence. The central area exhibited moderate ion concentrations, while the southeastern region had the highest calcium levels, possibly due to geological formations rich in calcium or human activities. The study highlights diverse hydrochemical characteristics of Effurun's borehole water, with some areas showing contamination beyond acceptable limits. Regular monitoring is essential to ensure safe drinking water and address potential health risks. The findings stress the need for improved water resource management and contamination control. This study provides a comprehensive spatial analysis of groundwater quality in Effurun, identifying specific areas at risk of contamination and offering data-driven recommendations for public health and sustainable water management.